2013
DOI: 10.1177/1094670513484508
|View full text |Cite
|
Sign up to set email alerts
|

“The People Make the Brand”

Abstract: Fit between an organization's brand and its employees, sometimes referred to as employee brand identification, has been highlighted as an important element in delivering service quality. This paper examines the people management practices directed both at potential and current employees which enhance this 'person-brand fit' and proposes that effective management of this can help reduce the persistent problem of social skills gaps in service organizations. A study of managers and customer-facing employees in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The firm's brand values should, therefore, be truthful, to reflect the company culture accurately and to represent an authentic employer brand. In doing so, making it easier to attract employees who share the same brand values and feel a fit between the organization and their own identity (Hurrell and Scholarios 2014).…”
Section: Employer Brand Identity and Employer Brand Imagementioning
confidence: 99%
See 1 more Smart Citation
“…The firm's brand values should, therefore, be truthful, to reflect the company culture accurately and to represent an authentic employer brand. In doing so, making it easier to attract employees who share the same brand values and feel a fit between the organization and their own identity (Hurrell and Scholarios 2014).…”
Section: Employer Brand Identity and Employer Brand Imagementioning
confidence: 99%
“…Employer brand image and employer brand desirability could, however, be a result of a combination of variables, including overall corporate brand, which may in part be influenced by online reviews. Previous research has shown that firms who communicate their core values in a manner that attracts like-minded employees, manage to create a differentiated employer brand and are better able to retain these employees (Hurrell and Scholarios 2014;Lievens and Highhouse 2003).…”
Section: Implications For Business Marketing Practicementioning
confidence: 99%
“…Probably, a brand may cease to be a symbol of the alienated state of a human consumer in relation to the commodity world, and therefore, in part, to his life world in general. On this basis it is possible to establish consensus in communication at the global level [8,10,17].…”
Section: Brand As a Cultural Form: From Innovation To Traditionmentioning
confidence: 99%
“…The promised service delivery and orientation are considered as some of the social skills of employees which are developed by the training and communication activities of an organisation to enhance the brand (Hurrell & Scholarios, 2014). These activities are the vital components of internal branding.…”
Section: Internal Brandingmentioning
confidence: 99%